Tingkat Keberhasilan Relokasi Ruang Bagi Pedagang Pada Penataan Pasar Marelan Kota Medan - Ahmad Nur Hafidzhi; Agung Sugiri (Jurusan Perencanaan Wilayah dan Kota, 2020)
Street Vendors or commonly referred to as street vendors are a group oftraders who sell by utilizing the area of the roadside to look for sustenance by holdingtheir wares. The importance of regulation and the need for structuring street vendors is arather troublesome job for almost all local governments in Indonesia. Almost all thearrangement and empowerment of street vendors often experience endless polemicproblems between the government and street vendors. The existence of street vendors iscaused by the inability of the formal sector to absorb labor which is increasinglyincreasing or as a result of the current urbanization of villagers who earn a fortune in thecity. The research method used in this study is a descriptive research method with aquantitative approach. The results of this study state that the traders' view of therelocation of the marelan market has been well implemented. because traders are quitesatisfied with the location and infrastructure facilities available at the Medan citymarelan market relocation, and traders assume after the arrangement, the merchant'sincome increases and the community's enthusiasm for shopping is greater. Based on theanalysis it is known that the relocation program that has been carried out by thegovernment has been successful in the physical, environmental and economic aspects ofthe traders.